Evaluasi Sebaran Longitudinal Sifat Fisika Dan Mekanika Dendrocalamus Asper Dan Gigantochoa Apus Menggunakan Mixed-Effect Modeling - Dwi Sukma Rini; Ichsan, Andi Chairil; Anwar, Hairil; Ningsih, Rima Vera; Khiarunnisa, Aulia; Ngadianto, Agus (BRIN Publishing, 2025)
Bamboo is an environmentally friendly construction material because it is renewable, lightweight, and possesses good mechanical strength. However, due to the lack of basic knowledge about the properties of bamboo culms, only a few species are commonly utililized. This study aims to investigate the longitudinal variation of physical and mechanical properties of Dendrocalamus asper and Gigantochloa apus that grow naturally on Lombok Island. Sampling was carried out by selecting 10 bamboo culms, aged 3-4 years old, from different clumps at each location. The tests conducted include moisture content, basic density, tangential and radial shrinkage, modulus of elasticity (MOE), and modulus of rupture (MOR). Statistical analysis was performed using R software, incorporating linear and non-linear mixed-effects models to evaluate longitudinal variations and the influence of individual and location on the distribution of bamboo properties. The results showed that the values for green moisture content, basic density, tangential and radial shrinkage at 1% moisture content change, MOE, and MOR for G. apus were 99.97%, 0.60 g/cm³, 0.29%, 0.35%, 8.27 GPa, and 108.80 MPa, respectively. Meanwhile, the values for D. apser were 108.13%, 0.58 g/cm³, 0.34%, 0.42%, 9.71 GPa, and 102.47 MPa, respectively. The longitudinal variation of moisture content in G. apus followed a linear pattern, while a logarithmic equation best described the variation in moisture content of D. asper, basic density, MOE, and MOR for both bamboo species. Additionally, the longitudinal variation in tangential and radial shrinkage for both species remained constant, following a linear equation with a y-intercept.